A capsaicin functional structure polymer microsphere liquid chromatography column and its preparation method and use

By using the polymer microspheres containing capsicin functional structures, the liquid chromatography columns were prepared by precipitation polymerization method, and the problem of Si-O bond dissolution of the liquid chromatography columns in the prior art under strong acid and strong alkali conditions was solved, achieving efficient separation and good reproducibility.

CN116037083BActive Publication Date: 2025-04-22OCEAN UNIV OF CHINA +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310032641.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-10
Publication Date
2025-04-22
Estimated Expiration
2043-01-10

AI Technical Summary

Technical Problem

The existing liquid chromatography columns dissolve Si-O bonds under strong acid and alkali conditions, resulting in chromatographic peak widening and tailing, affecting separation efficiency and reproducibility.

Method used

The liquid chromatography column was prepared by precipitation polymer microspheres using capsicin-containing functional structures, and the durability and high-pressure resistance of the column were improved by multi-layered coated structure.

Benefits of technology

It realizes efficient separation under strong acid and alkali conditions, reduces chromatographic peak widening and tailing phenomena, improves separation efficiency and reproducibility, and ensures the monodispersibility and uniform particle size distribution of the filler.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004123844530000091
    Figure GDA0004123844530000091
  • Figure HDA0004047843940000011
    Figure HDA0004047843940000011
  • Figure HDA0004047843940000012
    Figure HDA0004047843940000012
Patent Text Reader

Abstract

The invention relates to a liquid chromatography column containing a capsaicin functional structure polymer microsphere, a preparation method thereof and a use thereof. The preparation method of the liquid chromatography column containing a capsaicin functional structure polymer microsphere comprises the steps of preparing a spherical material, a first coating, a second coating and preparing a liquid chromatography column. The organic polymer microsphere has the advantages of good durability and high pressure resistance in an organic solvent. The preparation method ensures that the polymer microsphere is monodisperse, has a uniform particle size distribution, and has good pressure resistance. The preparation method of the invention is simple, has a stable process, uses a non-toxic and harmless solvent, and is environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of liquid chromatography separation. More specifically, the present invention relates to a capsaicin functional structure polymer microsphere liquid chromatography column, a preparation method of the liquid chromatography column, and a use of the liquid chromatography column. Background Art

[0002] As a powerful separation and analysis technology, chromatography plays an important role in many fields such as chemistry and chemical engineering, environmental science, food science, and life medicine. The separation mechanism of liquid chromatography is that the retention capacity of sample components in the stationary phase and the mobile phase is different, which leads to the difference in the elution speed of the target components from the chromatographic column, thus achieving the separation and detection of different components. Compared with traditional extraction and distillation methods, chromatography has the advantages of high separation efficiency, fast analysis speed and good selectivity, and is more suitable for the rapid separation of difficult-to-separate components; compared with chemical analysis methods, it is not limited by the chemical properties of the components to be separated, and can be used for the separation and analysis of structural analogs and isomers with similar chemical properties, especially realizing the simultaneous analysis and determination of multiple components, which is a goal that is difficult to achieve with traditional chemical analysis methods. Compared with spectroscopy and mass spectrometry, chromatography can achieve the simultaneous separation and analysis of multiple components.

[0003] As we all know, chromatographic columns are the core of chromatographic technology, and the quality of chromatographic separation performance depends on the type and properties of the stationary phase. In the chromatographic separation process, the stationary phase filler is the primary factor affecting the separation performance of liquid chromatography. Its research and development has attracted great attention from chromatographers and has always been one of the most active research directions in the field of chromatography. The preparation of high-selectivity and high-separation performance chromatographic stationary phases has always been the main driving force for the development of chromatographic technology. With the development of liquid chromatography technology, the types of liquid chromatography stationary phases have increased, and the structural composition of the stationary phase has also become diversified. The basic structure of the liquid chromatography stationary phase includes a support (matrix) and a functional group, in which the support provides the function of supporting the functional group, and the functional group provides the function of chromatographic retention and separation. As the supporting material of the stationary phase, the physical properties of the matrix, such as particle size, mechanical strength, specific surface area, and porosity, directly affect the distribution position of the functional group and the pressure resistance of the loaded chromatographic column, and the chemical properties of the matrix, such as chemical reactivity and chemical stability, directly affect the type of bondable functional groups and the difficulty of bonding. The two finally determine the retention characteristics and separation performance of the obtained stationary phase, such as column pressure and column efficiency. After long-term development, a large number of matrices and functional groups have been attempted to be used in the preparation and research of stationary phases.

[0004] The chromatographic columns currently used are mainly reverse-phase alkyl bonded silica gel columns, which have some problems: (1) Silica matrix microspheres are usually prepared by traditional emulsion polymerization, which is complicated and has a wide particle size distribution. They need to be screened at multiple levels to meet the needs of chromatographic fillers; (2) After bonding with alkyl chains, a certain amount of silanol groups still remain on the surface of silica gel, which will cause chromatographic peak broadening and tailing in the separation and analysis of alkaline compounds, seriously affecting the separation efficiency and reproducibility. Si-O bonds dissolve under strong acid and strong base conditions. In order to solve this problem, an organic polymer stationary phase that can replace silica gel was invented. Summary of the invention

[0005] Technical issues to be solved

[0006] The purpose of the invention is to provide a capsaicin functional structure polymer microsphere liquid chromatography column.

[0007] Another object of the present invention is to provide a method for preparing the capsaicin-containing functional structure polymer microsphere liquid chromatography column.

[0008] Another object of the present invention is to provide the use of the capsaicin-containing functional structure polymer microsphere liquid chromatography column.

[0009] Technical Solution

[0010] The present invention is achieved through the following technical solutions.

[0011] The invention relates to a method for preparing a capsaicin functional structure polymer microsphere liquid chromatography column.

[0012] The preparation steps of the preparation method are as follows:

[0013] A. Preparation of spherical materials

[0014] According to the weight ratio of pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution of 1:60-90:3-4:5-20:1000-2000, pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide and azobisisobutyronitrile initiator are added to the ethanol aqueous solution, mixed evenly, and polymerized under stirring, thereby obtaining a spherical material;

[0015] B. First coating

[0016] According to the weight ratio of spherical material, divinylbenzene, initiator and ethanol aqueous solution of 1: 0.1-0.5: 0.01-0.05: 2-5, divinylbenzene, azobisisobutyronitrile initiator and ethanol aqueous solution are added to the spherical material obtained in step A, and a first coating is performed for 1-3 hours under uniform stirring to obtain a spherical material with a first coating layer;

[0017] C. Second coating

[0018] According to the weight ratio of the spherical material with the first coating layer, divinylbenzene, N-vinylformamide, initiator and ethanol aqueous solution of 1:0.1-0.5:1-3:0.02-0.05:3-10, divinylbenzene, N-vinylformamide, azobisisobutyronitrile initiator and ethanol aqueous solution are added to the spherical material with the first coating layer, and a second coating is performed under uniform stirring, followed by filtering and drying to obtain a liquid chromatography stationary phase;

[0019] D. Preparative Liquid Chromatography Column

[0020] The liquid chromatography stationary phase obtained in step C is added to a mixed solution composed of methanol and isopropanol in a volume ratio of 1:1, dispersed evenly by using an ultrasonic device, and loaded into a chromatographic column; the same mixed solution is then taken and bubbles are removed by using an ultrasonic device as a displacement liquid; the displacement liquid is loaded using a high-pressure homogenizer column packing machine at a pressure of 40 to 45 MPa until the displacement liquid completely flows out, the pressure is reduced, the chromatographic column sieve plate and column head are installed, and then rinsed with methanol, thereby obtaining the liquid chromatography column.

[0021] According to another preferred embodiment of the present invention, in steps A to C, the concentration of the ethanol aqueous solution is 92-98% by weight.

[0022] According to another preferred embodiment of the present invention, in step A, the polymerization reaction is carried out at a temperature of 40 to 80° C. and a stirring speed of 600 to 1000 rpm for 2.0 to 5.0 hours.

[0023] According to another preferred embodiment of the present invention, in step A, the particle size of the spherical material is 2.0-3.0 μm.

[0024] According to another preferred embodiment of the present invention, in step B, the thickness of the first coating layer of the spherical material having the first coating layer is 0.1-0.3 μm.

[0025] According to another preferred embodiment of the present invention, in step C, the solid obtained by filtration is dried in a vacuum drying oven at a temperature of 60° C. until the water content thereof is less than 5.0% by weight.

[0026] According to another preferred embodiment of the present invention, in step C, the thickness of the second coating layer of the liquid chromatography stationary phase is 0.3-0.5 μm.

[0027] According to another preferred embodiment of the present invention, in step D, the methanol flushing is to flush the chromatographic column with methanol at a flow rate of 0.08-0.12 ml / min according to a methanol to chromatographic column bed volume ratio of 1:25-35.

[0028] The invention also relates to a capsaicin functional structure polymer microsphere liquid chromatography column prepared by the preparation method.

[0029] The invention also relates to the use of the capsaicin functional structure polymer microsphere liquid chromatography column in separating water-soluble vitamins B1, B2 or B6 by liquid chromatography.

[0030] The present invention will be described in more detail below.

[0031] The invention relates to the preparation of a liquid chromatography stationary phase. The liquid chromatography stationary phase is used to prepare a high-performance liquid chromatography column, and the high-performance liquid chromatography column is used to separate three water-soluble vitamins. Specifically, three monomers, namely, pyrogallic acid, divinylbenzene and N-hydroxymethyl acrylamide, are used to synthesize microspheres with a particle size of 2.0 to 3.0 μm through a precipitation polymerization mechanism under the initiation of azobisisobutyronitrile. Then, the microspheres are used as seeds, coated with a divinylbenzene intermediate layer, and then coated with a divinylbenzene and N-vinylformamide outer layer, and finally a liquid chromatography stationary phase is obtained.

[0032] The invention relates to a method for preparing a capsaicin functional structure polymer microsphere liquid chromatography column.

[0033] The preparation steps of the preparation method are as follows:

[0034] A. Preparation of spherical materials

[0035] According to the weight ratio of pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution of 1:60-90:3-4:5-20:1000-2000, pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide and azobisisobutyronitrile initiator are added to the ethanol aqueous solution, mixed evenly, and polymerized under stirring, thereby obtaining a spherical material;

[0036] The polymerization reaction of pyrogallol, divinylbenzene and N-hydroxymethyl acrylamide is as follows:

[0037] Accurately weigh pyrogallol, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution, add them into a 250 mL three-necked flask, stir to fully dissolve them, and then heat to react to obtain the spherical material.

[0038] In the present invention, when the dosage of divinylbenzene, N-hydroxymethyl acrylamide, azobisisobutyronitrile initiator and ethanol aqueous solution is within the range, if the dosage of pyrogallic acid is less than 60, the reaction product is not spherical; if the dosage of pyrogallic acid is more than 90, the dosage of capsaicin is too high, resulting in waste and more by-products; therefore, it is reasonable to use pyrogallic acid in an amount of 60 to 90, preferably 68 to 82, and more preferably 72 to 78;

[0039] When the dosage of pyrogallol, N-hydroxymethyl acrylamide, azobisisobutyronitrile initiator and ethanol aqueous solution is within the above range, if the dosage of divinylbenzene is less than 3, the particle size of the pellets is too small; if the dosage of divinylbenzene is more than 4, the pellets begin to agglomerate and are not dispersed enough; therefore, the dosage of divinylbenzene is suitable to be 3 to 4;

[0040] When the dosage of pyrogallol, divinylbenzene, azobisisobutyronitrile initiator and ethanol aqueous solution is within the range, if the dosage of N-hydroxymethyl acrylamide is less than 5, the size of the pellets is uneven and agglomerates occur; if the dosage of N-hydroxymethyl acrylamide is higher than 20, the sample dosage is too much and wastes; therefore, the dosage of N-hydroxymethyl acrylamide is appropriately 5 to 20, preferably 8 to 18, and more preferably 10 to 16;

[0041] When the dosage of pyrogallol, divinylbenzene, N-hydroxymethyl acrylamide and ethanol aqueous solution is within the range, if the dosage of azobisisobutyronitrile initiator is less than 5, no product is produced; if the dosage of azobisisobutyronitrile initiator is greater than 20, the dosage of initiator is too much, resulting in serious waste; therefore, the dosage of azobisisobutyronitrile initiator is appropriately 5 to 20, preferably 8 to 18, and more preferably 10 to 16;

[0042] When the dosage of pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide and azobisisobutyronitrile initiator is within the above range, if the dosage of ethanol aqueous solution is less than 1000, the particle size of the small balls becomes smaller; if the dosage of ethanol aqueous solution is more than 2000, the small balls agglomerate; therefore, the dosage of ethanol aqueous solution is 1000-2000, preferably 1200-1800, and more preferably 1350-1650;

[0043] The concentration of the ethanol aqueous solution used in the present invention is 92-98% by weight, and the subsequent steps also use the ethanol aqueous solution of the same concentration, so it will not be repeated below.

[0044] According to the present invention, the polymerization reaction is carried out at a temperature of 40 to 80° C. and a stirring speed of 600 to 1000 rpm for 2.0 to 5.0 hours.

[0045] In the present invention, when the stirring speed and the reaction time are within the range, if the polymerization temperature is lower than 80°C, the pellets do not react sufficiently, resulting in different sizes; if the polymerization temperature is higher than 80°C, the pellet size is uncontrollable; therefore, it is reasonable for the polymerization temperature to be 40 to 80°C, preferably 46 to 74°C; more preferably 52 to 68°C;

[0046] Similarly, when the polymerization temperature and reaction time are within the range, if the stirring speed is lower than 600 rpm, the pellets will agglomerate; if the stirring speed is higher than 1000 rpm, the speed is too high and is not conducive to pelletization; therefore, a stirring speed of 600 to 1000 rpm is appropriate, preferably 680 to 900 rpm; more preferably 720 to 840 rpm;

[0047] When the polymerization temperature and stirring speed are within the range, if the reaction time is shorter than 2.0 h, the pellets will not react sufficiently and the yield will be low; if the reaction time is longer than 5.0 h, the morphology of the pellets will change; therefore, a reaction time of 2.0 to 5.0 h is desirable, preferably 2.4 to 4.5 h; more preferably 2.8 to 4.0 h;

[0048] The pyrogallol used in the present invention is prepared according to the method described in CN 201410187252.X; the divinylbenzene, N-hydroxymethyl acrylamide and azobisisobutyronitrile used in the present invention are all products currently sold on the market, such as divinylbenzene sold by Aladdin under the trade name of divinylbenzene, N-hydroxymethyl acrylamide sold by Aladdin under the trade name of N-hydroxymethyl acrylamide, and azobisisobutyronitrile sold by Tianjin Damao under the trade name of azobisisobutyronitrile.

[0049] The present invention uses the equipment sold by Bruker of Germany under the trade name Fourier transform infrared spectrometer to analyze the spherical material. The analysis results are shown in the attached Figure 1 , of which 3000cm -1 is the NH stretching vibration peak of the amide group, 2900 cm -1 is the CH stretching vibration peak of the methyl group, 1200cm -1 It is the CO stretching vibration peak of N-hydroxymethyl acrylamide.

[0050] The present invention uses the SU8010 scanning electron microscope produced by Hitachi, Japan to observe the spherical material prepared in this step, and the observation results are listed in the attached Figure 2 ,The observation results show that the particle size of the spherical material is 2.0~3.0μm.

[0051] B. First coating

[0052] According to the weight ratio of spherical material, divinylbenzene, initiator and ethanol aqueous solution of 1: 0.1-0.5: 0.01-0.05: 2-5, divinylbenzene, azobisisobutyronitrile initiator and ethanol aqueous solution are added to the spherical material obtained in step A, and a first coating is performed for 1-3 hours under uniform stirring to obtain a spherical material with a first coating layer;

[0053] In the present invention, the spherical material, divinylbenzene and the initiator are reacted in an ethanol aqueous solution to form a first coating layer uniformly on the surface of the spherical material:

[0054] After the above step A is completed, divinylbenzene, initiator and ethanol aqueous solution are continuously added to the reaction system, and the reaction is continued under stirring under heating conditions.

[0055] In this step, when the amounts of the spherical material, the initiator and the ethanol aqueous solution are within the range, if the amount of divinylbenzene is less than 0.1, the surface of the sphere cannot be completely coated with a layer of divinylbenzene; if the amount of divinylbenzene is greater than 0.5, the coating is too thick; therefore, it is desirable that the amount of divinylbenzene is 0.1 to 0.5, preferably 0.1 to 0.4, and more preferably 0.2 to 0.4;

[0056] Similarly, when the amounts of the spherical material, the divinylbenzene initiator and the ethanol aqueous solution are within the range, if the amount of the azobisisobutyronitrile initiator is less than 0.01, the reaction cannot be fully carried out; if the amount of the azobisisobutyronitrile initiator is higher than 0.05, the amount of the initiator is too much, causing agglomeration; therefore, the amount of the azobisisobutyronitrile initiator is appropriately 0.01 to 0.05;

[0057] When the amounts of the spherical material, divinylbenzene and the initiator are within the above range, if the amount of the ethanol aqueous solution is less than 2, the particle size of the spheres cannot grow uniformly; if the amount of the ethanol aqueous solution is more than 5, the spheres agglomerate; therefore, the amount of the ethanol aqueous solution is appropriately 2 to 5, preferably 2.4 to 4.6, and more preferably 2.8 to 4.0;

[0058] The coating method used in this step and the subsequent steps is a conventional method for increasing the particle size of the pellets.

[0059] The present invention uses a device sold by Bruker, Germany under the trade name Fourier transform infrared spectrometer to analyze the spherical material with the first coating layer. The analysis results are shown in the attached Figure 1 .

[0060] The inventors used a SU8010 scanning electron microscope produced by Hitachi, Japan, to observe the spherical material with the first coating layer prepared in this step. The observation results are listed in the attached Figure 3The observation results show that the thickness of the first coating layer of the spherical material having the first coating layer is 0.1 to 0.3 μm.

[0061] The divinylbenzene, initiator and ethanol aqueous solution used in this step and subsequent steps are the same as those used in step A, so they are not repeated here.

[0062] C. Second coating

[0063] According to the weight ratio of the spherical material with the first coating layer, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution of 1: 0.1-0.5: 1-3: 0.02-0.05: 3-10, divinylbenzene, N-vinylformamide, azobisisobutyronitrile initiator and ethanol aqueous solution are added to the spherical material with the first coating layer, and a second coating is performed under uniform stirring, followed by filtering and drying to obtain a liquid chromatography stationary phase having the first coating layer and the second coating layer from the inside to the outside in sequence;

[0064] In the present invention, the spherical material having the first coating layer, divinylbenzene, N-hydroxymethyl acrylamide and azobisisobutyronitrile initiator are reacted in an ethanol aqueous solution to uniformly form a second coating layer on the surface of the first coating layer:

[0065] After the above reaction B is completed, divinylbenzene, N-vinylformamide, initiator and ethanol aqueous solution are continuously added to the reaction system, and the reaction is continuously stirred under heating conditions. After the reaction is completed, small balls having N-vinylformamide functional groups on the surface are synthesized.

[0066] The weight ratio of the spherical material, divinylbenzene, N-vinylformamide, initiator and ethanol aqueous solution is 1: 0.1-0.5: 1-3: 0.02-0.05: 3-10. When the amount of spherical material, N-vinylformamide, initiator and ethanol aqueous solution is within the range, if the amount of divinylbenzene is less than 0.1, the coating thickness is insufficient; if the amount of divinylbenzene is greater than 0.5, the coating is too thick; therefore, the amount of divinylbenzene is 0.1-0.5, which is reasonable; when the amount of spherical material, divinylbenzene, initiator and ethanol aqueous solution is within the range, if the amount of N-vinylformamide is less than 1, the functional groups on the surface of the spheres are too few; if the amount of N-hydroxymethyl acrylamide is greater than 3, the functional groups on the surface of the spheres are too many; therefore, the amount of N-hydroxymethyl acrylamide is 1-3, which is appropriate. When the amount of spherical material, divinylbenzene, N-vinylformamide and ethanol aqueous solution is within the range, if the amount of initiator is less than 0.02, the reaction is not sufficient; if the amount of initiator is higher than 0.05, the product is easy to agglomerate; therefore, the amount of initiator is 0.02-0.05 is appropriate; when the amount of spherical material, divinylbenzene, N-vinylformamide and initiator is within the range, if the amount of ethanol aqueous solution is lower than 3, the surface of the ball cannot grow uniformly; if the amount of ethanol aqueous solution is higher than 10, the ball agglomerates; therefore, the amount of ethanol aqueous solution is 3-10 is appropriate;

[0067] The N-vinylformamide used in the present invention is a product currently sold on the market, for example, a product sold by Aladdin Company under the trade name N-vinylformamide.

[0068] In this step, the filtered solids are dried in a vacuum drying oven at a temperature of 60° C. until the water content is less than 5.0% by weight. The vacuum drying oven used in the present invention is a product sold by Linpin Company under the trade name Vacuum Drying Oven. The water content of the dried solids is determined according to the gravimetric standard method. In the present invention, the main purpose of controlling the water content of the dried solids to less than 5% is to measure the yield of the sample to be 52%.

[0069] The present invention uses a device sold by Bruker, Germany under the trade name Fourier transform infrared spectrometer to analyze the liquid chromatography stationary phase. The analysis results are shown in the attached Figure 1 .

[0070] The present invention uses the SU8010 scanning electron microscope produced by Hitachi, Japan to observe the liquid chromatography stationary phase prepared in this step, and the observation results are listed in the attached Figure 4 , the observation results show that the thickness of the second coating layer of the liquid chromatography stationary phase is 0.3 to 0.5 μm.

[0071] D. Preparative Liquid Chromatography Column

[0072] The liquid chromatography stationary phase obtained in step C is added to a mixed solution composed of methanol and isopropanol in a volume ratio of 1:1, dispersed evenly by using an ultrasonic device, and loaded into a chromatographic column; the same mixed solution is then taken and bubbles are removed by using an ultrasonic device as a displacement liquid; the displacement liquid is loaded using a high-pressure homogenizer column packing machine at a pressure of 40 to 45 MPa until the displacement liquid completely flows out, the pressure is reduced, the chromatographic column sieve plate and column head are installed, and then rinsed with methanol, thereby obtaining the liquid chromatography column.

[0073] In the present invention, the mixed solution is used as a displacement fluid after the bubbles are removed. The main function of the displacement fluid is to adjust the column packing pressure by adjusting the flow rate of the displacement fluid.

[0074] According to the present invention, the methanol flushing is to flush the chromatographic column with methanol at a flow rate of 0.08-0.12 ml / min according to a volume ratio of methanol to the chromatographic column bed of 1:25-35.

[0075] The ultrasonic equipment and high-pressure homogenization column packing machine used in the present invention are products currently sold on the market, such as the ultrasonic equipment sold by Guanboshi Company under the trade name Ultrasonic Cleaner and the high-pressure homogenization column packing machine sold by Dalian Ripley Company under the trade name High-pressure Homogenization Column Packing Machine.

[0076] The invention also relates to a capsaicin functional structure polymer microsphere liquid chromatography column prepared by the preparation method.

[0077] The invention also relates to the use of the capsaicin functional structure polymer microsphere liquid chromatography column in separating water-soluble vitamins B1, B2 or B6 by liquid chromatography.

[0078] In order to evaluate the performance of the liquid chromatography column of the present invention in separating vitamins, according to the document DOI:10.1021 / jacs.9b03177, the following separation degree (Rs) formula was used to evaluate its separation efficiency:

[0079]

[0080] Where:

[0081] and are the retention times of two adjacent peaks, respectively;

[0082] W1 and W2 are the peak widths of two adjacent peaks.

[0083] (i) selecting water-soluble vitamins VB1, VB2 and VB6 to prepare a mixture aqueous solution having a content of 10 mg / L of vitamins VB1, VB2 and VB6 respectively;

[0084] (ii) Liquid chromatography conditions are as follows:

[0085] The mobile phase was methanol:NaAc-HAc buffer solution (pH=4.5)=30:70, the flow rate was 0.45 ml / min, and the column temperature was 20°C;

[0086] The high performance liquid chromatography column prepared by the present invention is used to separate the above vitamin mixture aqueous solution under a hydrophilic chromatography system. The separation results are shown in the attached Figure 5 , by the attached Figure 5 The separation degree (Rs) is calculated. According to the separation standard of the Chinese Pharmacopoeia, it can be determined from the separation degree (Rs) that the high performance liquid chromatography column prepared by the present invention can achieve effective separation of vitamins VB 1, VB 2, and VB 6, and can achieve baseline separation.

[0087] Beneficial Effects

[0088] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing organic polymer microspheres by precipitation polymerization, coating the microspheres, and obtaining a liquid chromatography stationary phase of organic polymer microspheres having amide groups, wherein the organic polymer microspheres have the advantages of good durability and high pressure resistance in organic solvents. The method ensures the monodispersity of the filler, uniform particle size distribution and good pressure resistance. The present invention has a simple preparation process, is easy to operate, uses a non-toxic and harmless solvent, and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0089] Attached Figure 1 It is an infrared spectrum of the spherical material (ball 1) in step A of the preparation method of the present invention, the spherical material with a first coating layer (ball 2) in step B, and the liquid chromatography stationary phase (ball 3) in step C;

[0090] Attached Figure 2 is a scanning electron microscope image of the spherical material in step A of the preparation method of the present invention;

[0091] Attached Figure 3 is a scanning electron microscope image of the spherical material having the first coating layer in step B of the preparation method of the present invention;

[0092] Attached Figure 4 is a scanning electron microscope image of the liquid chromatography stationary phase in step C of the preparation method of the present invention;

[0093] Attached Figure 5 It is a liquid chromatogram of separation and detection of VB1, VB 2 and VB6 by the preparative liquid chromatographic column of the present invention. DETAILED DESCRIPTION

[0094] The present invention will be better understood through the following examples.

[0095] Example 1: Preparation of a liquid chromatography column containing capsaicin functional polymer microspheres of the present invention

[0096] The implementation steps of this embodiment are as follows:

[0097] A. Preparation of spherical materials

[0098] According to the weight ratio of pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution of 1:80:3:15:1650, pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, azobisisobutyronitrile initiator are added to ethanol aqueous solution with a concentration of 98% by weight, mixed evenly, and polymerized for 5.0 hours at a temperature of 40° C. and a stirring speed of 800 rpm, thereby obtaining a spherical material;

[0099] The spherical material was analyzed using equipment sold by Bruker, Germany under the trade name Fourier Transform Infrared Spectrometer. The results of the analysis are shown in the attached Figure 1 ;

[0100] The present invention uses the SU8010 scanning electron microscope produced by Hitachi, Japan to observe the spherical material prepared in this step, and the observation results are listed in the attached Figure 2 ,The observation results show that the particle size of the spherical material is 2.0~3.0μm.

[0101] B. First coating

[0102] According to the weight ratio of spherical material, divinylbenzene, initiator and ethanol aqueous solution of 1:0.4:0.04:2, divinylbenzene, azobisisobutyronitrile initiator and ethanol aqueous solution with a concentration of 98% by weight are added to the spherical material obtained in step A, and the first coating is carried out for 2 hours under uniform stirring to obtain a spherical material with a first coating layer;

[0103] The spherical material with the first coating layer was analyzed using equipment sold by Bruker, Germany under the trade name Fourier Transform Infrared Spectrometer. The analysis results are shown in the attached Figure 1 .

[0104] The inventors used a SU8010 scanning electron microscope produced by Hitachi, Japan, to observe the spherical material with the first coating layer prepared in this step. The observation results are listed in the attached Figure 3 The observation results show that the thickness of the first coating layer of the spherical material having the first coating layer is 0.1 to 0.3 μm.

[0105] C. Second coating

[0106] According to the weight ratio of the spherical material with the first coating layer, divinylbenzene, N-vinylformamide, initiator and ethanol aqueous solution: 1:0.5:2:0.04:10, divinylbenzene, N-vinylformamide, azobisisobutyronitrile initiator and ethanol aqueous solution with a concentration of 98% by weight are added to the spherical material with the first coating layer, and a second coating is performed under uniform stirring, followed by filtering, and the solid obtained by filtration is dried in a vacuum drying oven at a temperature of 60° C. until the water content thereof is 4.8% by weight, thereby obtaining a liquid chromatography stationary phase;

[0107] The liquid chromatography stationary phase was analyzed using equipment sold by Bruker, Germany under the trade name Fourier Transform Infrared Spectrometer. The results of the analysis are given in the Appendix. Figure 1 .

[0108] The present invention uses the SU8010 scanning electron microscope produced by Hitachi, Japan to observe the liquid chromatography stationary phase prepared in this step, and the observation results are listed in the attached Figure 4 , the observation results show that the thickness of the second coating layer of the liquid chromatography stationary phase is 0.3 to 0.5 μm.

[0109] D. Preparative Liquid Chromatography Column

[0110] The liquid chromatography stationary phase obtained in step C is added to a mixed solution composed of methanol and isopropanol in a volume ratio of 1:1, dispersed evenly by using an ultrasonic device, and loaded into a chromatographic column; the same mixed solution is then taken and the bubbles therein are removed by using an ultrasonic device as a displacement liquid; the displacement liquid is loaded into a high-pressure homogenizer column packing machine at a pressure of 45 MPa until the displacement liquid completely flows out, the pressure is reduced, the chromatographic column sieve plate and column head are installed, and then the methanol is rinsed at a flow rate of 0.08 ml / min in a volume ratio of methanol to the chromatographic column bed of 1:35, thereby obtaining the liquid chromatography column.

[0111] According to the method described in the specification of this application, the liquid chromatography column prepared in this example was used to separate the water-soluble vitamin B1, B2 or B6 mixture. The separation results are shown in the attached Figure 5 , by the attached Figure 5 It can be calculated that the separation degree (Rs) of VB1 and VB6 is 1.59, and the separation degree of VB6 and VB2 is 1.94. Vitamins VB1, VB2, and VB6 are effectively separated.

[0112] Example 2: Preparation of the Capsaicin-containing polymer microsphere liquid chromatography column of the present invention

[0113] The implementation steps of this embodiment are as follows:

[0114] A. Preparation of spherical materials

[0115] According to the weight ratio of pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution of 1:60:4:5:1000, pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, azobisisobutyronitrile initiator are added to the ethanol aqueous solution with a concentration of 92% by weight, mixed evenly, and polymerized for 2.0 hours at a temperature of 80° C. and a stirring speed of 600 rpm, thereby obtaining a spherical material;

[0116] The spherical material was analyzed using equipment sold by Bruker, Germany, under the trade name Fourier Transform Infrared Spectrometer, and the results were consistent with those of the attached Figure 1 similar;

[0117] The present invention uses a SU8010 scanning electron microscope produced by Hitachi, Japan to observe the spherical material prepared in this step, and the observation results are consistent with the attached Figure 2 Similarly, the observation results show that the particle size of the spherical material is 2.0-3.0 μm.

[0118] B. First coating

[0119] According to the weight ratio of spherical material, divinylbenzene, initiator and ethanol aqueous solution of 1:0.5:0.01:5, divinylbenzene, azobisisobutyronitrile initiator and ethanol aqueous solution with a concentration of 92% by weight are added to the spherical material obtained in step A, and the first coating is carried out for 1 hour under uniform stirring to obtain a spherical material with a first coating layer;

[0120] The spherical material with the first coating layer was analyzed using equipment sold by Bruker, Germany under the trade name Fourier Transform Infrared Spectrometer, and the analysis results were consistent with the attached Figure 1 similar.

[0121] The inventors used a SU8010 scanning electron microscope produced by Hitachi, Japan, to observe the spherical material with the first coating layer prepared in this step, and the observation results were consistent with those in the attached drawings. Figure 3 Similarly, the observation results show that the thickness of the first coating layer of the spherical material having the first coating layer is 0.1 to 0.3 μm.

[0122] C. Second coating

[0123] According to the weight ratio of the spherical material with the first coating layer, divinylbenzene, N-vinylformamide, initiator and ethanol aqueous solution: 1:0.3:1:0.02:5, divinylbenzene, N-vinylformamide, azobisisobutyronitrile initiator and ethanol aqueous solution with a concentration of 92% by weight are added to the spherical material with the first coating layer, and a second coating is performed under uniform stirring, followed by filtering, and the solid obtained by filtration is dried in a vacuum drying oven at a temperature of 60° C. until the water content thereof is 4.6% by weight, thereby obtaining a liquid chromatography stationary phase;

[0124] The liquid chromatography stationary phase was analyzed using equipment sold by Bruker, Germany, under the trade name Fourier Transform Infrared Spectrometer, and the results were consistent with those of the attached Figure 1 similar.

[0125] The present invention uses a SU8010 scanning electron microscope produced by Hitachi, Japan to observe the liquid chromatography stationary phase prepared in this step, and the observation results are consistent with those of the attached Figure 4 Similarly, the observation results indicate that the thickness of the second coating layer of the liquid chromatography stationary phase is 0.3-0.5 μm.

[0126] D. Preparative Liquid Chromatography Column

[0127] The liquid chromatography stationary phase obtained in step C is added to a mixed solution composed of methanol and isopropanol in a volume ratio of 1:1, and is dispersed evenly using an ultrasonic device, and loaded into a chromatographic column; the same mixed solution is then taken and the bubbles therein are removed using an ultrasonic device as a displacement liquid; the displacement liquid is loaded using a high-pressure homogenizer column loading machine at a pressure of 40 MPa until the displacement liquid completely flows out, the pressure is reduced, the chromatographic column sieve plate and column head are installed, and then the methanol is rinsed at a flow rate of 0.10 ml / min in a volume ratio of methanol to the chromatographic column bed of 1:25, thereby obtaining the liquid chromatography column.

[0128] According to the method described in the specification of this application, the liquid chromatography column prepared in this embodiment is used to separate the water-soluble vitamin B1, B2 or B6 mixture, and the separation results are consistent with the attached Figure 5 Close, by the Figure 5 It can be calculated that the separation degree (Rs) of VB1 and VB6 is 1.59, and the separation degree of VB6 and VB2 is 1.94. Vitamins VB1, VB2, and VB6 are effectively separated.

[0129] Example 3: Preparation of the Capsaicin-containing polymer microsphere liquid chromatography column of the present invention

[0130] The implementation steps of this embodiment are as follows:

[0131] A. Preparation of spherical materials

[0132] According to the weight ratio of pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution of 1:90:4:20:2000, pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, azobisisobutyronitrile initiator are added to ethanol aqueous solution with a concentration of 96% by weight, mixed evenly, and polymerized for 4.0 hours at a temperature of 54° C. and a stirring speed of 800 rpm, thereby obtaining a spherical material;

[0133] The spherical material was analyzed using equipment sold by Bruker, Germany, under the trade name Fourier Transform Infrared Spectrometer, and the results were consistent with those of the attached Figure 1 similar;

[0134] The present invention uses a SU8010 scanning electron microscope produced by Hitachi, Japan to observe the spherical material prepared in this step, and the observation results are consistent with the attached Figure 2 Similarly, the observation results show that the particle size of the spherical material is 2.0-3.0 μm.

[0135] B. First coating

[0136] According to the weight ratio of spherical material, divinylbenzene, initiator and ethanol aqueous solution of 1:0.3:0.05:4, divinylbenzene, azobisisobutyronitrile initiator and ethanol aqueous solution with a concentration of 96% by weight are added to the spherical material obtained in step A, and the first coating is carried out for 2 hours under uniform stirring to obtain a spherical material with a first coating layer;

[0137] The spherical material with the first coating layer was analyzed using equipment sold by Bruker, Germany under the trade name Fourier Transform Infrared Spectrometer, and the analysis results were consistent with the attached Figure 1 similar.

[0138] The inventors used a SU8010 scanning electron microscope produced by Hitachi, Japan, to observe the spherical material with the first coating layer prepared in this step, and the observation results were consistent with those in the attached drawings. Figure 3 Similarly, the observation results show that the thickness of the first coating layer of the spherical material having the first coating layer is 0.1 to 0.3 μm.

[0139] C. Second coating

[0140] According to the weight ratio of the spherical material with the first coating layer, divinylbenzene, N-vinylformamide, initiator and ethanol aqueous solution: 1:0.1:3:0.05:3, divinylbenzene, N-vinylformamide, azobisisobutyronitrile initiator and ethanol aqueous solution with a concentration of 96% by weight are added to the spherical material with the first coating layer, and a second coating is performed under uniform stirring, followed by filtering, and the solid obtained by filtration is dried in a vacuum drying oven at a temperature of 60° C. until the water content thereof is 4.9% by weight, thereby obtaining a liquid chromatography stationary phase;

[0141] The liquid chromatography stationary phase was analyzed using equipment sold by Bruker, Germany, under the trade name Fourier Transform Infrared Spectrometer, and the results were consistent with those of the attached Figure 1 similar.

[0142] The present invention uses a SU8010 scanning electron microscope produced by Hitachi, Japan to observe the liquid chromatography stationary phase prepared in this step, and the observation results are consistent with those of the attached Figure 4 Similarly, the observation results indicate that the thickness of the second coating layer of the liquid chromatography stationary phase is 0.3-0.5 μm.

[0143] D. Preparative Liquid Chromatography Column

[0144] The liquid chromatography stationary phase obtained in step C is added to a mixed solution composed of methanol and isopropanol in a volume ratio of 1:1, and is dispersed evenly using an ultrasonic device, and loaded into a chromatographic column; the same mixed solution is then taken and the bubbles therein are removed using an ultrasonic device as a displacement liquid; the displacement liquid is loaded using a high-pressure homogenizer column loading machine at a pressure of 45 MPa until the displacement liquid completely flows out, the pressure is reduced, the chromatographic column sieve plate and column head are installed, and then the methanol is rinsed at a flow rate of 0.12 ml / min in a volume ratio of methanol to the chromatographic column bed of 1:28, thereby obtaining the liquid chromatography column.

[0145] According to the method described in the specification of this application, the liquid chromatography column prepared in this embodiment is used to separate the water-soluble vitamin B1, B2 or B6 mixture, and the separation results are consistent with the attached Figure 5 Close, by the Figure 5 It can be calculated that the separation degree (Rs) of VB1 and VB6 is 1.59, and the separation degree of VB6 and VB2 is 1.94. Vitamins VB1, VB2, and VB6 are effectively separated.

[0146] Example 4: Preparation of the Capsaicin-containing polymer microsphere liquid chromatography column of the present invention

[0147] The implementation steps of this embodiment are as follows:

[0148] A. Preparation of spherical materials

[0149] According to the weight ratio of pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution of 1:70:3:10:1350, pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, azobisisobutyronitrile initiator are added to ethanol aqueous solution with a concentration of 94% by weight, mixed evenly, and polymerized for 3.0 hours at a temperature of 66° C. and a stirring speed of 1000 rpm, thereby obtaining a spherical material;

[0150] The spherical material was analyzed using equipment sold by Bruker, Germany, under the trade name Fourier Transform Infrared Spectrometer, and the results were consistent with those of the attached Figure 1 similar;

[0151] The present invention uses a SU8010 scanning electron microscope produced by Hitachi, Japan to observe the spherical material prepared in this step, and the observation results are consistent with the attached Figure 2 Similarly, the observation results show that the particle size of the spherical material is 2.0-3.0 μm.

[0152] B. First coating

[0153] According to the weight ratio of spherical material, divinylbenzene, initiator and ethanol aqueous solution of 1:0.1:0.03:3, divinylbenzene, azobisisobutyronitrile initiator and ethanol aqueous solution with a concentration of 94% by weight are added to the spherical material obtained in step A, and the first coating is carried out for 3 hours under uniform stirring to obtain a spherical material with a first coating layer;

[0154] The spherical material with the first coating layer was analyzed using equipment sold by Bruker, Germany under the trade name Fourier Transform Infrared Spectrometer, and the analysis results were consistent with the attached Figure 1 similar.

[0155] The inventors used a SU8010 scanning electron microscope produced by Hitachi, Japan, to observe the spherical material with the first coating layer prepared in this step, and the observation results were consistent with those in the attached drawings. Figure 3 Similarly, the observation results show that the thickness of the first coating layer of the spherical material having the first coating layer is 0.1 to 0.3 μm.

[0156] C. Second coating

[0157] According to the weight ratio of the spherical material with the first coating layer, divinylbenzene, N-vinylformamide, initiator and ethanol aqueous solution: 1:0.4:2:0.03:8, divinylbenzene, N-vinylformamide, azobisisobutyronitrile initiator and ethanol aqueous solution with a concentration of 94% by weight are added to the spherical material with the first coating layer, and a second coating is performed under uniform stirring, followed by filtering, and the solid obtained by filtration is dried in a vacuum drying oven at a temperature of 60° C. until the water content thereof is 4.8% by weight, thereby obtaining a liquid chromatography stationary phase;

[0158] The liquid chromatography stationary phase was analyzed using equipment sold by Bruker, Germany, under the trade name Fourier Transform Infrared Spectrometer, and the results were consistent with those of the attached Figure 1 similar.

[0159] The present invention uses a SU8010 scanning electron microscope produced by Hitachi, Japan to observe the liquid chromatography stationary phase prepared in this step, and the observation results are consistent with those of the attached Figure 4 Similarly, the observation results show that the thickness of the second coating layer of the liquid chromatography stationary phase is 0.3-0.5 μm.

[0160] D. Preparative Liquid Chromatography Column

[0161] The liquid chromatography stationary phase obtained in step C is added to a mixed solution composed of methanol and isopropanol in a volume ratio of 1:1, and is evenly dispersed using an ultrasonic device, and loaded into a chromatographic column; the same mixed solution is then taken and the bubbles are removed using an ultrasonic device as a displacement liquid; the displacement liquid is loaded using a high-pressure homogenizer column loading machine at a pressure of 40 MPa until the displacement liquid completely flows out, the pressure is reduced, the chromatographic column sieve plate and column head are installed, and then the methanol is rinsed at a flow rate of 0.10 ml / min in a volume ratio of methanol to the chromatographic column bed of 1:32, thereby obtaining the liquid chromatography column.

[0162] According to the method described in the specification of this application, the liquid chromatography column prepared in this embodiment is used to separate the water-soluble vitamin B1, B2 or B6 mixture, and the separation results are consistent with the attached Figure 5 Close, by the Figure 5 It can be calculated that the separation degree (Rs) of VB1 and VB6 is 1.59, and the separation degree of VB6 and VB2 is 1.94. Vitamins VB1, VB2, and VB6 are effectively separated.

Claims

1. A method for preparing a capsaicin functional structure polymer microsphere liquid chromatography column, characterized in that The preparation steps of the preparation method are as follows: A. Preparation of spherical materials According to the weight ratio of pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide, initiator and ethanol aqueous solution of 1:60-90:3-4:5-20:1000-2000, pyrogallic acid, divinylbenzene, N-hydroxymethyl acrylamide and azobisisobutyronitrile initiator are added to the ethanol aqueous solution, mixed evenly, and polymerized under stirring, thereby obtaining a spherical material; B. First coating According to the weight ratio of spherical material, divinylbenzene, initiator and ethanol aqueous solution of 1: 0.1-0.5: 0.01-0.05: 2-5, divinylbenzene, azobisisobutyronitrile initiator and ethanol aqueous solution are added to the spherical material obtained in step A, and a first coating is performed for 1-3 hours under uniform stirring to obtain a spherical material with a first coating layer; C. Second coating According to the weight ratio of the spherical material with the first coating layer, divinylbenzene, N-vinylformamide, initiator and ethanol aqueous solution: 1: 0.1-0.5: 1-3: 0.02-0.05: 3-10, divinylbenzene, N-vinylformamide, azobisisobutyronitrile initiator and ethanol aqueous solution are added to the spherical material with the first coating layer, and a second coating is performed under uniform stirring, followed by filtering and drying to obtain a liquid chromatography stationary phase; D. Preparative Liquid Chromatography Column The liquid chromatography stationary phase obtained in step C is added to a mixed solution composed of methanol and isopropanol in a volume ratio of 1:1, dispersed evenly by using an ultrasonic device, and loaded into a chromatographic column; the same mixed solution is then taken and bubbles are removed by using an ultrasonic device as a displacement liquid; the displacement liquid is loaded using a high-pressure homogenizer column packing machine at a pressure of 40 to 45 MPa until the displacement liquid completely flows out, the pressure is reduced, the chromatographic column sieve plate and column head are installed, and then rinsed with methanol, thereby obtaining the liquid chromatography column.

2. The preparation method according to claim 1, characterized in that In step A to step C, the concentration of the ethanol aqueous solution is 92-98% by weight.

3. The preparation method according to claim 1, characterized in that In step A, the polymerization reaction is carried out at a temperature of 40-80° C. and a stirring speed of 600-1000 rpm for 2.0-5.0 hours.

4. The preparation method according to claim 1, characterized in that In step A, the particle size of the spherical material is 2.0-3.0 μm.

5. The preparation method according to claim 1, characterized in that In step B, the first coating thickness of the spherical material having the first coating layer is 0.1 to 0.3 μm.

6. The preparation method according to claim 1, characterized in that In step C, the solid obtained by filtration is dried in a vacuum drying oven at 60° C. until the water content thereof is less than 5.0% by weight.

7. The preparation method according to claim 1, characterized in that In step C, the thickness of the second coating layer of the liquid chromatography stationary phase is 0.3-0.5 μm.

8. The preparation method according to claim 1, characterized in that In step D, the methanol flushing is to flush the chromatographic column with methanol at a flow rate of 0.08-0.12 ml / min according to a methanol to column bed volume ratio of 1:25-35.

9. A liquid chromatography column of polymer microspheres containing capsaicin functional structure prepared according to the preparation method described in any one of claims 1 to 8.

10. Use of the capsaicin functional structure polymer microsphere liquid chromatography column according to claim 9 in separating water-soluble vitamins B1, B2 or B6 by liquid chromatography.

Citation Information

Patent Citations

  • Monofunctional acrylamide compound with capsaicinoid functional structure and preparation method and application thereof

    CN103951576A

  • Hydrophobic association polymer with various loop-structure side chains and preparation method and application thereof

    CN106496411A

  • Dendritic mixed mode HPLC(High Performance Liquid Chromatography) filler based on dopamine as well as preparation method application thereof

    CN108906009A